(untitled) (The Journal of Psychology and Sociology, 2016)
Today, in front of all - to each person, society and the state faces challenges in their adaptation to life circumstances in the flow of change. In these circumstances, a person must acquire certain knowledge and skills successfully operating infor mation, have qualities that allow it to improve the knowledge in accordance with modern information technology have a broad outlook on the functions, objectives and significance of the existence of the information society in the modern world. The appearance and the further development of the information society and the glo balization of social relations set new goals for the current socialization of the individual, and so in the first place, are put forward creative, creativity, availability of analytical, sys tems thinking, high level of stress, adaptive capacity and tolerant social behavior. Informa tion Culture as part of the general culture, as the socio-cultural basis of life and activity of the individual in modern society, is the key to ensuring social security for present and future generations. It defines fundamental principles of lawful behavior of persons in a society undergoing rapid and frequent change, as well as a great instability. In addition, its functions can be expressed in the formation of the foundations of personal and social security, the development of a flexible, sustainable, critical thinking. One of the key fac tors of successful socialization of the person in favor of the existence of the information culture. The high level of information culture promotes socialization and is a prerequisite for its development in today’s transformed society. The article reviewed and analyzed at the same time the concept of the term «in formation culture», it is given a new interpretation arising in the emerging information society, provides an overview of the conditions of its formation. Today there is every reason to talk about the formation of a new information culture, as part of the general culture of mankind. It should be based on knowledge of the information environment and the laws of its functioning, the ability to navigate the information flows.